KEANEKARAGAMAN JENIS KUPU-KUPU PADA EKOSISTEM HUTAN RAWA AIR TAWAR DAN HUTAN DATARAN RENDAH DI DESA BELITANG DUA KECAMATAN BELITANG KABUPATEN SEKADAU - Saputra, Marjan; anto, Eri; Siahaan, Sarma (Universitas Tanjungpura, 2014)
The objective of this study was to determine the diversity of butterfly in freshwater swamp forest ecosystems and lowland forest in the village of two district Belitang . Belitang Sekadau regency . Butterflies potential data is indispensable for the development and management of the conservation and conservation of rare species of butterflies and endemic found . So it can be for managing the data and its development in the conservation of the rare butterfly and endemic. The results showed there were 24 species of butterflies are found in freshwater swamp forest ecosystems and lowland forest in two village of Belitang. Belitang Sekadau regency . Index of butterfly species diversity of habitats in the two studies have a range of values ??is from 1.00 to 1.17. Abundance index type (e) butterfly habitat in each study had a range of values ??from 0.71 to 0.85. Dominance index for each habitat research have range of values ??(C) = 0.06 to 0.11. Wealth type butterflies in lowland forest that is (D) = 6.63, while for freshwater swamp forest is (D) = 9.47. The similarity index type butterfly in two habitats have in common with the type of value that is ( CN ) = 0.35 or 35 % . Keyword : Butterfly, diversity, ecosystem freshwater swamp forest and lowland forest